Peningkatan Literasi Digital dan Penguasaan Life Skill melalui Penerapan Konsep Ijarah ‘ala ‘Amal pada Virtual Assistant - Sa’diah, Diah Siti; Rusmani (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2024)
The digital ecosystem is currently evolving rapidly, impacting various fields, including professions. Islamic boarding schools (Pondok Pesantren or Ponpes) as religious educational institutions face challenges in keeping up with the times, particularly in enhancing digital literacy competencies and leveraging them for career development in the virtual world. One potential profession is that of a Virtual Assistant (VA), which, in the context of Sharia economic law, falls under the concept of ijarah ‘alal ‘amal (contract of services). Ponpes al-Sa’adah in Bandung Regency envisions developing the potential of its graduates and the entire academic community through the utilization of digital literacy. Based on this premise, a Student Creativity Program (PKM) is necessary and aims to: (1) analyze the potential for developing digital literacy and life skills among the younger generation at Ponpes al-Sa’adah; (2) examine community engagement strategies to enhance digital literacy and mastery of life skills through the application of the ijarah ‘alal ‘amal concept in the VA profession within Ponpes al-Sa’adah; (3) analyze the implications of this program on improving digital literacy and life skills for the younger generation. This study employs the "ACTORS" theory by Steve MacCulay and Sarah Cook, using the ABCD method. The conclusions of this PKM are: (1) ponpes al-Sa’adah has significant potential to foster work ethics, digital literacy, and life skills through the application of the ijarah concept in Virtual Assistant roles; (2) community engagement strategies involve training on the ijarah concept, an understanding of Virtual Assistants, and the necessary skills to become a VA; (3) participants can understand and effectively practice VA skills while comprehending the application of the ijarah bil ‘amal concept in the VA profession.